Effects of Intravenous Pharmacopuncture with Harmonizing and Releasing Formulas on Hepatic Recovery after Partial Hepatectomy in Rats - Hyun-Jin Lee; Chan Lee; Yun-Kyoung Yim (Medical Association of Pharmacopuncture Institute, 2017)
The objective of this study was to find out the effect of intravenous pharmacopuncture on hepatic recovery after partial hepatectomy in rats. Male Sprague-Dawley rats were randomly divided into five groups: normal group, control group, saline group, and two experimental groups. Except for those in the normal group, the rats underwent partial hepatectomy. Those in the control group did not receive any treatment. Those in the saline group received an intravenous injection with saline. Those in the two experimental groups received intravenous pharmacopuncture with SihoJigak-tang or DanchiSoyo-san extracts (10 mg/kg). Serum total bilirubin and liver regeneration rate were measured on Day 7 after partial hepatectomy. Intravenous pharmacopuncture with SihoJigak-tang significantly increased the liver regeneration rate, and intravenous pharmacopuncture with DanchiSoyo-san significantly decreased serum total billirubin after partial hepatectomy.